Nonthermal tetravinylsilane plasma used for thin‐film deposition: Plasma chemistry controls thin‐film chemistry. Issue 4 (28th December 2021) - Cech, Vladimir; Branecky, Martin
Abstract: The power dependence of the plasma species in nonthermal tetravinylsilane plasmas used for thin‐film deposition is investigated by mass spectrometry. Mass spectra analysis reveals the dominant carbon‐ and silicon‐containing species responsible for film growth. The deposition rate determined by in situ spectroscopic ellipsometry correlates with the flux of these species chemisorbed on the film surface if distinct sticking coefficients are taken into account. Then, the carbon to silicon ratio in the deposited film strongly correlates with the C/Si flux ratio for the various power‐controlled plasmas. Similarly, the concentration of vinyl groups incorporated into the deposited film and the proportion of sp 2 hybridization of the carbon network correlate with the fluxes of the respective plasma species. Abstract : It is found that the dominant plasma species are responsible for the elemental composition and chemical structure of the deposited films. These species are the result of the electron impact dissociation of precursor molecules and chemical processes on the surface of the growing film. A better understanding of the relationships between plasma chemistry and thin‐film chemistry allows the construction of a thin film tailored to a given application.